Criminal Liability Analysis of Supervisory Consultants in Construction Project Accidents: A Literature Review on the Principle of Culpa in Supervision and the Implementation of Law No. 2 of 2017 - Reza Senjaya (International Journal Labs, 2025)
Workplace accidents in Indonesia's construction projects remain a critical legal and social issue. When incidents occur, public attention often focuses on contractors, while the criminal liability of supervisory consultants receives limited scholarly attention. This article analyzes the basis of criminal liability of supervisory consultants through the principle of culpa in supervisione (negligence in supervision) under Law No. 2 of 2017 on Construction Services, Government Regulation No. 50 of 2012 on the Occupational Safety and Health Management System (SMK3), and the Ministry of Public Works and Housing (PUPR) Regulation on Construction Safety Management System (SMKK). The study adopts a normative legal method using statutory, conceptual, and case approaches with references from 2020–2025 literature. The results show that supervisory consultants may be criminally liable if proven negligent in fulfilling their supervisory duties and if their negligence has a causal connection with a workplace accident. The article introduces a three-layer compliance model (normative, technical, and evidential) as a preventive framework for minimizing criminal risks. The findings provide theoretical and practical implications for policymakers and construction professionals to strengthen accountability within Indonesia's construction law framework.